Grievance Redress Mechanisms in the Public Sector: A Literature Review - Pande, Suchi; Hossain, Naomi (Open Government Partnership and Accountability Research Center, 2022)
Grievance redress mechanisms (GRMs) in the public sector are institutionalized processes designed to enable people to complain about and seek redress for services they rightfully should have received. This paper reviews evidence on GRMs from around the world, focusing on mechanisms attached to public services and programs in the Global South, where they are relatively new and emerging fast. GRMs matter in particular in the Global South because they are increasingly widespread and found in multilateral aid programs, across national governments, within specific programs and services, as well as in the private sector. GRMs are expected to improve public service efficiency, effectiveness, and fairness by giving people a systematic means of seeking redress for governance failures, and they have strong potential to improve accountability to the most excluded and marginalized people, who tend to find it most difficult to make claims on their state. The review includes a simple framework for understanding the key elements of successful GRMs, as identified through the review process. These are: • Citizen capacity to complain • State capacity to respond • Proactive transparency The review concludes with key research questions to improve our understanding of how GRMs work and could be better designed and implemented.
Keywords: #Reviews & Framing / Revisões e Organização; *tagged; G - Rest of the World / Resto do Mundo; L - english / inglês; accountability / responsabilização; governance / governação; mecanismos de reclamação / grievance redress mechanisms; ⛔ No DOI found

What actually is social accountability? - Aston, Thomas (Medium, 2021)
Figuring out “what is the work?” we actually do sounds like a simple task, but in fact, it’s surprisingly difficult.
Keywords: #Reviews & Framing / Revisões e Organização; *indexed; G - Rest of the World / Resto do Mundo; L - english / inglês; access to services / acesso a serviços; accountability / responsabilização

Accountability Ecosystems: The Evolution of a Keyword - Halloran, Brendan (Accountability Research Center, 2021)
Efforts to strengthen the accountability of the governing to the governed go back millennia. However, in the past decade there has been a renewed debate about how to advance public accountability. One domain where this conversation has taken place is that of efforts funded by donors (government development agencies and private philanthropies), primarily in the Global South and implemented by a set of national and international actors, including NGOs, private sector project implementors, and international institutions. Unfortunately, much donor-funded work has been underpinned by an understanding of accountability grounded in optimistic assumptions, particularly around the role of transparency and information technology. Early efforts by Rosie McGee and John Gaventa to take stock of this work highlighted the lack of theories of change grounded in a more nuanced, holistic and politically-informed understanding of accountability. Others began questioning the dominant ‘transparency + participation = accountability’ formulation that underpinned many projects; and most of them were just that, projects: start date, end date, work plan, logical framework, funding proposal, budget, etc. It was at the beginning of this discussion about what it takes to achieve real accountability that the term ‘Accountability Ecosystem’ started being used by a few individuals and organizations. The organization I worked for at the time, the Transparency and Accountability Initiative (TAI), had picked up the term, potentially from the organization I work for now, the International Budget Partnership (IBP).[i] I saw the term as a way to advance a more holistic and dynamic way to talk about the interaction of accountability actors, mechanisms and efforts in a given context, and a deliberate step away from more simplistic, linear formulations.
Keywords: #Reviews & Framing / Revisões e Organização; G - Rest of the World / Resto do Mundo; L - english / inglês; accountability / responsabilização

Estimating the cost of implementing a facility and community score card for maternal and newborn care service delivery in a rural district in Uganda - Ssebagereka, Anthony; Apolot, Rebecca Racheal; Nyachwo, Evelyne Baelvina; Ekirapa-Kiracho, Elizabeth (International Journal for Equity in Health, 2021)
This paper aimed at estimating the resources required to implement a community Score Card by a typical rural district health team in Uganda, as a mechanism for fostering accountability, utilization and quality of maternal and child healthcare service.
Keywords: #Reviews & Framing / Revisões e Organização; *indexed; *tagged; G - Rest of the World / Resto do Mundo; Health PEA; L - english / inglês; access to services / acesso a serviços; accountability / responsabilização; community scorecard (CSC) / cartão de pontuação comunitária (CPC); gender / género; health - maternal and child / saúde - materno-infantil; health / saúde; youth / juventude